Checking noise correlations for safer two-way quantum key distribution - Shamsul Shaari, Jesni; Lucamarini, Marco; Mancini, Stefano (Springer, 2014)
We check for noise correlations between forward and backward paths in two-way quantum key distribution, which leads to reduced potentialities for an eavesdropper since she can only hide herself behind uncorrelated (natural) noise. The security enhancement is evaluated through the ratio of eavesdropper’s information and legitimate users’ information achievable against the most relevant individual attacks.